HYDRO BIOLOGICAL STUDIES OF AN IRRIGATION TANK WITH REFERENCE TO THE CULTURE OF LARGE MURREL , CHANNA MARULIUS (HAMILTON) AND STRIPED MURREL CHANNA STRIATUS (BLOCH) - P, GEORGE J; VENUGOPAL, G; VENKATESHVARAN, K; HINGORNI, H G (Fishery Technology, 2017)
The importants of selection of species for culture according to the ecological niches and fish food organisms is highlighted with respect to the fox sugar , an irrigation tank.The tank was infested wih sub merged vegetation asa well as minnows and weed fishes which randerded the tank unsuitable for the culture of indian major carps.therefore .the tank was stocked with 8000 fingerlings of channas marulius and C.striatus during 1981 by the local fishermen co-operative society.only partial harvest was possible during 1982because of the highwater level. The final harvest was done by the members of the society using convential traps,drag nets and castnet in april Â - may 1985. The yeild obtained was 3640 kg during the culture period of 20 months.